Relationship of the prevalence of dental erosion on risk factors in adolescents - Pacheco Arana, Brenda Rosa (2024)
The objective is to establish the relationship between the prevalence of dental erosion and risk factors in adolescents. The method is relational, observational, prospective and transversal with a non-experimental design. 56 adolescents from 13 to 16 years old were evaluated; For the clinical evaluation, the Basic Erosive Wear Examination (BEWE) index and a structured questionnaire related to extrinsic factors were used. Results. The Kolmogorov-Smirnov normality test was performed, where it was found that the data do not follow a normal distribution, which is why the non-parametric Rho Spearman statistical test was applied with a p-value of 0.000. Conclusion. A statistically significant and directly proportional correlation was found between extrinsic factors such as habits, habit and frequency of consumption of acidic foods, acidic drinks and intrinsic factors such as gastroesophageal alterations.